Upaya Meningkatkan Motivasi Belajar Matematika Siswa SMP Menggunakan Model Pembelajaran Problem Based Learning (PBL) (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2020)
This Classroom Action Research aims to increase motivation to learnmathematics using the Problem Based Learning (PBL) model for studentsof class VIII-A of SMP Negeri 2 Parenggean. This study consisted of twocycles, with research subjects of 25 students. Each cycle consists of fourstages, namely planning, implementing actions, observing andreflecting. The research instrument used consisted of observations of theimplementation of learning sheets, affective assessment instruments usingstudents 'mathematics learning motivation questionnaires and multiplechoice tests to see students' cognitive learning outcomes in mathematics. Data analysis was performed by comparing the initial conditions before theaction, the end of the first cycle and the end of the second cycle qualitativelyand quantitatively. In the first cycle, of student motivation showed a score of82.80 (average) consisting of 1 student (4%) in the low category, 13students (52%) on average, 9 students (36%) in the high category and 2students (8%) ) in very high category and PBL learning implementationreached 79.68%. In the second cycle students' learning motivationscores 93.44 (high) with 4 students (16%) in the average category, 15students (60%) in the high category and 6 students (24%) in the very highcategory and 90.63% in the implementation of learning. . The resultsshowed that mathematics learning with PBL models can increase students'motivation to learn mathematics.